Effect of applying NPK 17+17+17 fertilizer and GDM liquid organic fertilizer (POC) on growth and production of cucumber (Cucumis sativus L.) - Rosalyne, Irawaty; Situmeang, Ringkop; Sinaga, Hengky Fernando (Central Research Institute For Agriculture, 2024)
This research used a factorial Randomized Block Design (RAK), with two treatment factors, where the first factor was the administration of a dose of NPK 17+17+17 Kuda Sakti (N) fertilizer consisting of 4 levels, namely, N0 = No Treatment, N1 = 150 kg /ha (60 g/plot), N2 = 300 kg/ha (120 g/plot), N3 = 450 kg/ha (180 g/plot). The second factor is the dose of liquid organic fertilizer (POC) GDM (G) which consists of 4 levels, namely, G0 = No Treatment, G1 = 6.7 ml POC GDM/1 liter of water, G2 = 13.4 ml POC GDM/1 liter of water, G3 = 20 ml POC GDM/ 1 liter of water. The parameters observed were primary stem length (cm), number of fruit per plant (fruit), number of fruit per plot (fruit), fruit weight per plant (kg), and fruit weight per plot (kg). The interaction of NPK 17+17+17 fertilizer treatment and GDM liquid organic fertilizer (POC) had a significant effect on primary stem length at 14, 28, and 42 DAT, number of fruit per plant, fruit weight per sample, and fruit weight per plot, but had no effect real impact on the number of fruits per plot. The interaction between the two treatments with the highest mean for each parameter, namely primary stem length at 14, 28, and 42 HST respectively, was highest at N3G3 (15.14 cm), (120.08 cm), (184.12 cm), number of fruit per plant The highest number is found in N3G3 (10.00 pieces), the highest number of fruit per plot is found in N3G3 (39.00 pieces), the heaviest fruit weight per plant is found in N3G3 (2.73 kg), the heaviest fruit weight per plot is found in N3G3 ( 14.76 kg). The parameters observed in this research included: Plant Height (cm) at 30, 45 HST, Number of Branches, Number of Pods per Plant (fruit), Pod Weight per Plant (g) and Pod Weight per Plot (g).